Income Inequality and Labour Income Share in CIS Countries: Trends, Impacts and Causes - Kurmangaliyeva, L.; Aimagambetov, E.; Spanova, B.; Myrzhykbayeva, A. (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of this paper is to study trends, reasons of income inequality and labour income share in CIS countries. Methods: The study relies on the use of secondary research methods. It is a research method that focuses on using the existing published documents to generate insights into the object of the research. Findings: In CIS countries, employment remains the major source of income where the prospect of having a job has higher implications in terms of income inequality. Various changes have occurred in income inequality in recent years due to the global financial crisis and the pandemic. It, therefore, occurs that both the macroeconomic policies and the labor market policies have facilitated the situation. Conclusions: The study has focused on the use of secondary research methods where publications by the IMF and the World Bank have been given the top priority and used in conjunction with other sources from legitimate sources. It has been established that CIS region is characterized by countries that are deeply immersed in the situation of rising income inequalities and declining labor shares.